2005
DOI: 10.1038/ng1628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations in CUL7 in 3-M syndrome

Abstract: Intrauterine growth retardation is caused by maternal, fetal or placental factors that result in impaired endovascular trophoblast invasion and reduced placental perfusion. Although various causes of intrauterine growth retardation have been identified, most cases remain unexplained. Studying 29 families with 3-M syndrome (OMIM 273750), an autosomal recessive condition characterized by severe pre- and postnatal growth retardation, we first mapped the underlying gene to chromosome 6p21.1 and then identified 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
145
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 14 publications
3
145
0
Order By: Relevance
“…We found that the substrate recognizing component of this complex, Fbx29, does not directly interact with p53, but associates indirectly with p53 in a Cul7-dependent manner. In agreement with our findings, the Cul7 domains responsible for p53 and FBX29 binding are not overlapping (25,27).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that the substrate recognizing component of this complex, Fbx29, does not directly interact with p53, but associates indirectly with p53 in a Cul7-dependent manner. In agreement with our findings, the Cul7 domains responsible for p53 and FBX29 binding are not overlapping (25,27).…”
Section: Discussionsupporting
confidence: 82%
“…observed in mice deficient for other negative regulators of p53, as MDM2 and MDMX (30,32,33). In line with a positive role of Cul7 in unperturbed cell proliferation mutational inactivation of Cul7 causes the 3-M syndrome, an autorecessive form of dwarfism characterized by pre-and postnatal growth retardation (27). According to our results, it is possible that the increase in p53 activity, which may result from mutated, nonfunctional Cul7, contributes to the 3-M syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…14 We have shown earlier that nonsense and missense CUL7 mutations (R1445X and H1464P) impaired the ability of CUL7 to recruit ROC1, suggesting that impaired ubiquitination may play a role in the pathogenesis of prenatal growth retardation in humans. 6 In addition, the association of pre-and postnatal growth retardation with skeletal changes in 3M syndrome suggests that CUL7 may play a specific role in the endochondral ossification process. In keeping with this, analysis of the femoral growth plate of the 3M foetus revealed an increased in chondrocyte density and a defect in matrix production in the resting and proliferative zones.…”
Section: Discussionmentioning
confidence: 99%
“…1 -5 Studying a series of 29 families, we have previously mapped the disease locus to chromosome 6p21.1, and identified diseasecausing mutations in the CUL7 gene. 6 Here, we report the molecular analysis of the CUL7 gene in a series of 33 additional cases and the identification of mutations in 23/33 cases including one paternal isodisomy of chromosome 6. The absence of CUL7 mutation in the other 10/33 cases and the exclusion of the 6p21.1 locus in consanguineous families support the genetic heterogeneity of the 3M syndrome.…”
mentioning
confidence: 99%
“…In addition, we have demonstrated that CUL1 promotes the invasion of human trophoblast cells and is significantly downregulated in the placentas from PE patients (Zhang et al 2013). Combined with the studies from other labs like the implication of Cullin 7 in 3-M syndrome and the Yakut short stature syndrome (Huber et al 2005, Maksimova et al 2007), characterized by pre-and post-natal growth retardation, we found that the Cullin family of proteins play very special roles during human placentation. To obtain a whole picture of the function of Cullin family proteins in human placenta development and pregnancy-related diseases, we further studied the roles of other Cullin family members, like CUL3, in placenta development.…”
Section: Introductionmentioning
confidence: 59%